Business strategy and sustainability - Aras, Güler; Crowther, David (Developments in corporate governance and responsibility ;, 2012)
This volume examines the word that's on everybodys lips in business, in government and in society - sustainability. There are of course many aspects of sustainability which might be considered to reflect Brundtlands three pillars of economic, environmental and social sustainability. Others of course have different definitions which include such things as governance or supply chain management. Nevertheless business has recognised the significance of the concept and is responding by developing strategies to cope, although some would say that this is little more than window dressing. The debate continues however as to just what is meant by the term sustainability as far as business is concerned and how can this be achieved. This book is designed to address this debate and set it within the context of the global business and societal environment.